Oral delivery of indinavir using mPEG-PCL nanoparticles: preparation, optimization, cellular uptake, transport and pharmacokinetic evaluation. Issue 1 (4th December 2019) - Kurd, Masoumeh; Sadegh Malvajerd, Soroor; Rezaee, Saeed; Hamidi, Mehrdad; Derakhshandeh, Katayoun
Abstract: Introduction: Indinavir (IDV) is a potent HIV protease inhibitor used in the treatment of human immunodeficiency virus (HIV). IDV is a weak base with limited aqueous solubility in its unprotonated form; therefore, solubility of IDV in the gastrointestinal tract fluids is the rate-limiting step of its absorption and onset of action. However, in many cases, drugs are not absorbed well in the gastrointestinal tract; polymer nanoparticles were recognized as an effective carrier system for drug encapsulation and are now studied as a vehicle for oral delivery of insoluble compounds. Preparation of methoxy poly (ethylene glycol)-poly (e-caprolactone) (mPEG-PCL) nanoparticles is among the strategies to overcome low bioavailability of drugs with poor aqueous solubility. Materials and method: The structure of the copolymers was characterized using 1 H NMR, FTIR, DSC and GPC techniques. IDV loaded mPEG- PCL nanoparticles prepared by emulsification solvent evaporation method were optimized using D-optimal experimental design and were characterized by various techniques such as DLS, DSC, XRD, AFM and SEM. Using Caco-2 cells as a cellular model, we studied the cellular uptake and transport. Results: In vivo pharmacokinetic studies were performed in rats. The plasma AUC (0– t ), t 1/2 and C max of IDV-mPEG-PCL NPs were increased by 5.30, 5.57 and 1.37 fold compared to the IDV solution, respectively. Conclusion: The results of this study are promising for the use of biodegradable polymeric nanoparticles to improve oral drug delivery.